2011
DOI: 10.1017/s0030605310001791
|View full text |Cite
|
Sign up to set email alerts
|

Human livelihoods and protected areas in Gabon: a cross-sectional comparison of welfare and consumption patterns

Abstract: Understanding the role that protected areas play in the livelihood security of local communities is essential to ensure that local people are not left shouldering the costs of what is a public good, and to help maintain robust local and national constituencies for biodiversity conservation. To provide baseline data for a longitudinal study on the effects of newly established national parks on human livelihoods in Gabon we conducted a cross-sectional study that compared livelihood indicators between communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…Foerster et al [70] report that purchasing power is lower in villages closer to PAs in Gabon. Cardozo [71] conducted a questionnaire-based site comparison of communities inside and outside AllpahuayoMishara National Reserve, Peru and reported changes in income and livelihood diversity.…”
Section: Livelihood Strategiesmentioning
confidence: 99%
“…Foerster et al [70] report that purchasing power is lower in villages closer to PAs in Gabon. Cardozo [71] conducted a questionnaire-based site comparison of communities inside and outside AllpahuayoMishara National Reserve, Peru and reported changes in income and livelihood diversity.…”
Section: Livelihood Strategiesmentioning
confidence: 99%
“…Household wealth is also typically associated with bushmeat consumption, with richer households consuming more in urban households in Rio Muni [19] although poorer households consume more in rural Equatorial Guinea [13]. Education is negatively associated with consumption of certain wild mammals in rural Gabon [18]. Bushmeat hunters enter protected areas from outside but to a decreasing extent with distance from their settlements [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, household size has positive effects on bushmeat consumption on Bioko Island, West Africa [17, see also 6] but negative effects in Gabon [18]. Household wealth is also typically associated with bushmeat consumption, with richer households consuming more in urban households in Rio Muni [19] although poorer households consume more in rural Equatorial Guinea [13].…”
Section: Introductionmentioning
confidence: 99%
“…A narrow view of wellbeing is unlikely to reflect reality as improvements in measured aspects could be offset by undetected declines in others. For example, one study found that, compared to controls, households in a national park showed improved health indicators but lower income and less trust in their neighbors (Foerster et al 2011). Measuring only income could have led to the conclusion that proximity to the park decreased wellbeing, although the reality was much more complex.…”
Section: Discussionmentioning
confidence: 99%